Frequent nocturnal awakening in early life is associated with nonatopic asthma in children - Kozyrskyj, A.; Kendall, Garth; Zubrick, Stephen; Newnham, J.; Sly, Peter (European Respiratory Society, 2009)
Frequent nocturnal awakening in early life is associated with nonatopic asthma in children Holdings more options Author(s): Kozyrskyj AL (Kozyrskyj, A. L.)1,2, Kendall GE (Kendall, G. E.)3,4,6, Zubrick SR (Zubrick, S. R.)3,5,6, Newnham JP (Newnham, J. P.)7, Sly PD (Sly, P. D.)3,6 Source: EUROPEAN RESPIRATORY JOURNAL Volume: 34 Issue: 6 Pages: 1288-1295 Published: DEC 2009 Times Cited: 1 References: 54 Citation Map Abstract: Sleep deprivation has become a common phenomenon of the Western world and is associated with a variety of medical problems in children. This retrospective longitudinal analysis of a community-based birth cohort was undertaken to determine whether frequent nocturnal awakening during early life was associated with the development of childhood asthma.2,398 children born to mothers recruited from the antenatal clinics of a single hospital in Perth, Australia during 1989-1991 were followed up at years 1, 2, 3, 6, 8, 10 and 14. Parent-completed questionnaires were analysed. The odds ratio for asthma at age 6 and 14 yrs in children with frequent nocturnal awakening during the first 3 yrs after birth was determined from multiple logistic regression.Following adjustment for asthma risk factors, co-sleeping and family stress, persistent nocturnal awakening was associated with nonatopic asthma at age 6 and 14 yrs (at age 14 yrs: OR 2.18, 95% CI 1.15-4.13) but not with atopic asthma.We found an increased risk of nonatopic asthma in children following frequent nocturnal awakening during the first 3 yrs of life. These hypothesis-generating data suggest the need for further systematic study of the effects of disordered sleep in early life on the development of asthma. Document Type: Article Language: English Author Keywords: Asthma; child; infant; Raine study; sleep KeyWords Plus: NECROSIS-FACTOR-ALPHA; SHORT SLEEPING HOURS; EARLY-CHILDHOOD; BRONCHIAL RESPONSIVENESS; CIRCADIAN-RHYTHMS; ATOPIC-DERMATITIS; TERM INFANTS; BIRTH COHORT; CORTISOL; STRESS Reprint Address: Kozyrskyj, AL (reprint author), , 8226A Aberhart Ctr,11402 Univ Ave, Edmonton, AB T6G 2J3 Canada Addresses: 1. Univ Alberta, Dept Paediat, Edmonton, AB Canada 2. Univ Manitoba, Dept Community Hlth Sci, Dept Paediat & Child Hlth, Winnipeg, MB R3T 2N2 Canada 3. Telethon Inst Child Hlth Res, Perth, WA Australia 4. Curtin Univ Technol, Sch Nursing & Midwifery, Perth, WA Australia 5. Curtin Univ Technol, Ctr Dev Hlth, Perth, WA Australia 6. Univ Western Australia, Ctr Child Hlth Res, Perth, WA 6009 Australia 7. Univ Western Australia, Sch Womens & Infants Hlth, Perth, WA 6009 Australia E-mail Addresses: kozyrsky@ualberta.ca Funding Acknowledgement: Funding Agency Grant Number Raine Medical Research Foundation, University of Western Australia, Perth National Health and Medical Research Council, Canberra, Australia [Show funding text] Sincere thanks are due to all Study families, without whose participation this research could not have been conducted. Many thanks are also extended to the Western Australian Pregnancy Cohort (Raine) Study investigators and research staff. The authors wish to acknowledge the Raine Medical Research Foundation, University of Western Australia, Perth, Australia and the National Health and Medical Research Council, Canberra, Australia in funding the establishment and continuation of this birth cohort. Finally, A.L. Kozyrskyj would like to thank M. Berinson and all of the other staff at the Telethon Institute for Child Health Research (TICHR), Perth, for their research Support of this project, which was completed by A.L. Kozyrskyj during her research leave at TICHR. The research was conducted independently of the funding agency. Publisher: EUROPEAN RESPIRATORY SOC JOURNALS LTD, 442 GLOSSOP RD, SHEFFIELD S10 2PX, ENGLAND Subject Category: Respiratory System IDS Number: 530XD ISSN: 0903-1936 DOI: 10.1183/09031936.00040509 Cited by: 1 This article has been cited 1 times (from Web of Science). Rosen D, Frischer T Innovation, or reverse causation? EUROPEAN RESPIRATORY JOURNAL 34 6 1215-1216 DEC 2009 [ view all 1 citing articles ] Related Records: Find similar records based on shared references (from Web of Science). [ view related records ] References: 54 View the bibliography of this record (from Web of Science). Additional information View the journal's impact factor (in Journal Citation Reports) View the journal's Table of Contents (in Current Contents Connect) Suggest a correction If you would like to improve the quality of this product by suggesting corrections, please fill out this form. << Back to results list Record 1 of 1 Record from Web of Science® Output Record Step 1: Authors, Title, Source plus Abstract Full Record plus Cited Reference Step 2: [How do I export to bibliographic management software?] Save to other Reference Software Save to BibTeX Save to HTML Save to Plain Text Save to Tab-delimited (Win) Save to Tab-delimited (Mac) View in ???? English Please give us your feedback on using ISI Web of Knowledge.Acceptable Use PolicyCopyright © 2009 Thomson Reuters Frequent nocturnal awakening in early life is associated with nonatopic asthma in children Holdings more options Author(s): Kozyrskyj AL (Kozyrskyj, A. L.)1,2, Kendall GE (Kendall, G. E.)3,4,6, Zubrick SR (Zubrick, S. R.)3,5,6, Newnham JP (Newnham, J. P.)7, Sly PD (Sly, P. D.)3,6 Source: EUROPEAN RESPIRATORY JOURNAL Volume: 34 Issue: 6 Pages: 1288-1295 Published: DEC 2009 Times Cited: 1 References: 54 Citation Map Abstract: Sleep deprivation has become a common phenomenon of the Western world and is associated with a variety of medical problems in children. This retrospective longitudinal analysis of a community-based birth cohort was undertaken to determine whether frequent nocturnal awakening during early life was associated with the development of childhood asthma.2,398 children born to mothers recruited from the antenatal clinics of a single hospital in Perth, Australia during 1989-1991 were followed up at years 1, 2, 3, 6, 8, 10 and 14. Parent-completed questionnaires were analysed. The odds ratio for asthma at age 6 and 14 yrs in children with frequent nocturnal awakening during the first 3 yrs after birth was determined from multiple logistic regression.Following adjustment for asthma risk factors, co-sleeping and family stress, persistent nocturnal awakening was associated with nonatopic asthma at age 6 and 14 yrs (at age 14 yrs: OR 2.18, 95% CI 1.15-4.13) but not with atopic asthma.We found an increased risk of nonatopic asthma in children following frequent nocturnal awakening during the first 3 yrs of life. These hypothesis-generating data suggest the need for further systematic study of the effects of disordered sleep in early life on the development of asthma. Document Type: Article Language: English Author Keywords: Asthma; child; infant; Raine study; sleep KeyWords Plus: NECROSIS-FACTOR-ALPHA; SHORT SLEEPING HOURS; EARLY-CHILDHOOD; BRONCHIAL RESPONSIVENESS; CIRCADIAN-RHYTHMS; ATOPIC-DERMATITIS; TERM INFANTS; BIRTH COHORT; CORTISOL; STRESS Reprint Address: Kozyrskyj, AL (reprint author), , 8226A Aberhart Ctr,11402 Univ Ave, Edmonton, AB T6G 2J3 Canada Addresses: 1. Univ Alberta, Dept Paediat, Edmonton, AB Canada 2. Univ Manitoba, Dept Community Hlth Sci, Dept Paediat & Child Hlth, Winnipeg, MB R3T 2N2 Canada 3. Telethon Inst Child Hlth Res, Perth, WA Australia 4. Curtin Univ Technol, Sch Nursing & Midwifery, Perth, WA Australia 5. Curtin Univ Technol, Ctr Dev Hlth, Perth, WA Australia 6. Univ Western Australia, Ctr Child Hlth Res, Perth, WA 6009 Australia 7. Univ Western Australia, Sch Womens & Infants Hlth, Perth, WA 6009 Australia E-mail Addresses: kozyrsky@ualberta.ca Funding Acknowledgement: Funding Agency Grant Number Raine Medical Research Foundation, University of Western Australia, Perth National Health and Medical Research Council, Canberra, Australia [Show funding text] Sincere thanks are due to all Study families, without whose participation this research could not have been conducted. Many thanks are also extended to the Western Australian Pregnancy Cohort (Raine) Study investigators and research staff. The authors wish to acknowledge the Raine Medical Research Foundation, University of Western Australia, Perth, Australia and the National Health and Medical Research Council, Canberra, Australia in funding the establishment and continuation of this birth cohort. Finally, A.L. Kozyrskyj would like to thank M. Berinson and all of the other staff at the Telethon Institute for Child Health Research (TICHR), Perth, for their research Support of this project, which was completed by A.L. Kozyrskyj during her research leave at TICHR. The research was conducted independently of the funding agency. Publisher: EUROPEAN RESPIRATORY SOC JOURNALS LTD, 442 GLOSSOP RD, SHEFFIELD S10 2PX, ENGLAND Subject Category: Respiratory System IDS Number: 530XD ISSN: 0903-1936 DOI: 10.1183/09031936.00040509 Cited by: 1 This article has been cited 1 times (from Web of Science). Rosen D, Frischer T Innovation, or reverse causation? EUROPEAN RESPIRATORY JOURNAL 34 6 1215-1216 DEC 2009 [ view all 1 citing articles ] Related Records: Find similar records based on shared references (from Web of Science). [ view related records ] References: 54 View the bibliography of this record (from Web of Science). Additional information View the journal's impact factor (in Journal Citation Reports) View the journal's Table of Contents (in Current Contents Connect) Suggest a correction If you would like to improve the quality of this product by suggesting corrections, please fill out this form. << Back to results list Record 1 of 1 Record from Web of Science® Output Record Step 1: Authors, Title, Source plus Abstract Full Record plus Cited Reference Step 2: [How do I export to bibliographic management software?] Save to other Reference Software Save to BibTeX Save to HTML Save to Plain Text Save to Tab-delimited (Win) Save to Tab-delimited (Mac) View in ???? English Please give us your feedback on using ISI Web of Knowledge.Acceptable Use PolicyCopyright © 2009 Thomson Reuters kkkkkCopyright ©ERS Journals Ltd 2009Frequent nocturnal awakening in early life is associated with nonatopic asthma in childrenA. L. Kozyrskyj1,2, G. E. Kendall3,4,5, S. R. Zubrick3,5,6, J. P. Newnham7 and P. D. Sly3,51 Dept of Paediatrics, University of Alberta, Edmonton, AB, 2 Dept of Community Health Sciences, Dept of Paediatrics and Child Health, University of Manitoba, Winnipeg, MB, Canada. 3 Telethon Institute for Child Health Research, 4 School of Nursing and Midwifery, Curtin University of Technology, 6 Centre for Developmental Health, Curtin University of Technology, 5 Centre for Child Health Research, University of Western Australia, and 7 School of Women's and Infants' Health, University of Western Australia, Perth, Australia.CORRESPONDENCE: A. L. Kozyrskyj, 8226a Aberhart Centre, 11402 University Ave, Edmonton, AB T6G 2J3, Canada. E-mail: kozyrsky@ualberta.caKeywords: Asthma, child, infant, Raine study, sleepReceived: March 12, 2009Accepted August 12, 2009Sleep deprivation has become a common phenomenon of the Western world and is associated with a variety of medical problems in children. This retrospective longitudinal analysis of a community-based birth cohort was undertaken to determine whether frequent nocturnal awakening during early life was associated with the development of childhood asthma.2,398 children born to mothers recruited from the antenatal clinics of a single hospital in Perth, Australia during 1989–1991 were followed up at years 1, 2, 3, 6, 8, 10 and 14. Parent-completed questionnaires were analysed. The odds ratio for asthma at age 6 and 14 yrs in children with frequent nocturnal awakening during the first 3 yrs after birth was determined from multiple logistic regression.Following adjustment for asthma risk factors, co-sleeping and family stress, persistent nocturnal awakening was associated with nonatopic asthma at age 6 and 14 yrs (at age 14 yrs: OR 2.18, 95% CI 1.15–4.13) but not with atopic asthma.We found an increased risk of nonatopic asthma in children following frequent nocturnal awakening during the first 3 yrs of life. These hypothesis-generating data suggest the need for further systematic study of the effects of disordered sleep in early life on the development of asthma.This article has been cited by other articles: Home page Eur Respir JHome pageD. Rosen and T. FrischerInnovation, or reverse causation?Eur. Respir. J., December 1, 2009; 34(6): 1215 - 1216.[Full Text] [PDF] HOME HELP FEEDBACK SUBSCRIPTIONS ARCHIVE SEARCH TABLE OF CONTENTSCopyright © 2009 by the European Respiratory Society.